Musculoskeletal Infection in Pediatrics: Assessment of the 2018 International Consensus Meeting on Musculoskeletal Infection. (18th December 2019) - Cooper, Alexus M.; Shope, Alexander J.; Javid, Mahzad; Parsa, Ali; Chinoy, Muhammad Amin; Parvizi, Javad
Abstract : Abstract: The Second International Consensus Meeting (ICM) on Musculoskeletal Infection was held in July 2018 in Philadelphia, Pennsylvania. This meeting involved contributions from an international multidisciplinary consortium of experts from orthopaedic surgery, infectious disease, pharmacology, rheumatology, microbiology, and others. Through strict delegate engagement in a comprehensive 13-step consensus process based on the Delphi technique, evidence-based consensus guidelines on musculoskeletal infection were developed. The 2018 ICM produced updates to recommendations from the inaugural ICM that was held in 2013, which primarily focused on periprosthetic infection of the hip and the knee, and added new guidelines with the expansion to encompass all subspecialties of orthopaedic surgery. The following proceedings from the pediatrics section are an overview of the ICM consensus recommendations on the prevention, diagnosis, and treatment of pediatric musculoskeletal infection.